2009
DOI: 10.1364/oe.17.014322
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic ellipsometry applied to phase transitions in solids: possibilities and limitations

Abstract: The possibilities of in situ spectroscopic ellipsometry applied to phase transitions investigation in oxide thin films and crystals are examined in this work, along with the use of various parameters calculated from ellipsometric data (band gap energy Eg, refractive index n and surface roughness) together with the directly measured main ellipsometric angles psi and Delta, for the detection of phase transitions. The efficiency of spectroscopic ellipsometry on "surface" phase transition and its sensitivity to su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 50 publications
1
15
0
Order By: Relevance
“…SE has long been recognized as a powerful method for the characterization of thin films and their inhomogeneity. It has already been applied to refractive index depth profile studies of oxynitride SiO 2 N x films (Callard et al, 1998;Nguyen et al, 1996;Snyder et al, 1992;Rivory, 1998;) (additionally confirmed by chemical etching (Callard et al, 1998)), lead silicate glass (Trolier-McKinstry and Koh, 1998), oxidized copper layers (Nishizawa et al, 2004), polymers (Guenther et al, 2002), semiconductor indium tin oxide (ITO) films (Losurdo, 2004;Morton et al, 2002), sol-gel PZT thin films (Aulika et al, 2009) confirmed by TEM and EDX, and RF-sputtered self-polarized PZT thin films , and was confirmed by discharge optical emission spectroscopy (GD-OES) and pyroelectric profile measurements by the laser intensity-modulation method (LIMM) (Deineka et al, January, 2001;Suchaneck et al, 2002). SE has also been applied to the study of ion implantation depth profiles in silicon wafers and confirmed by RBS (Boher et al, 1996;Fried et al, 2004).…”
Section: Depth Profile Detection Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…SE has long been recognized as a powerful method for the characterization of thin films and their inhomogeneity. It has already been applied to refractive index depth profile studies of oxynitride SiO 2 N x films (Callard et al, 1998;Nguyen et al, 1996;Snyder et al, 1992;Rivory, 1998;) (additionally confirmed by chemical etching (Callard et al, 1998)), lead silicate glass (Trolier-McKinstry and Koh, 1998), oxidized copper layers (Nishizawa et al, 2004), polymers (Guenther et al, 2002), semiconductor indium tin oxide (ITO) films (Losurdo, 2004;Morton et al, 2002), sol-gel PZT thin films (Aulika et al, 2009) confirmed by TEM and EDX, and RF-sputtered self-polarized PZT thin films , and was confirmed by discharge optical emission spectroscopy (GD-OES) and pyroelectric profile measurements by the laser intensity-modulation method (LIMM) (Deineka et al, January, 2001;Suchaneck et al, 2002). SE has also been applied to the study of ion implantation depth profiles in silicon wafers and confirmed by RBS (Boher et al, 1996;Fried et al, 2004).…”
Section: Depth Profile Detection Methodsmentioning
confidence: 99%
“…This technique does not require a large size of the sample; it is enough to have a size of ~ 5×5 mm. In situ spectral ellipsometry studies allow detecting phase transition in thin films and surfaces (Dejneka et al, 2009), as well as of the interface what is very important for thin film and crystal studies. For advanced optoelectronics and bandgap engineering applications is important to investigate the relationship between the microstructure, sample preparation conditions & optical properties.…”
Section: Spectroscopic Ellipsometrymentioning
confidence: 99%
See 3 more Smart Citations